Polar mesosphere winter echoes by ESRAD, EISCAT and lidar - Kirkwood, S.; Barabash, Victoria; Belova, E.; Nilsson, H.; Rao, T.N.; Stebel, K.; Blum, U.; Fricke, K-H.; Osepian, A.; Chilson, Phillip B. (British Astronomical Society, 2002)
The ESRAD 52 MHz MST radar (67° 53 ‘ N, 21 ° 06 ‘ E) has observed thin layers of enhanced radar echoes in the winter mesosphere during several recent solar proton events. The detection of these polar mesosphere winter echoes (PMWE) is generally found to correlates well with low values of λ (the ratio of negative ion density to electron density). However PMWE are found to persist for values of λ up to ~100. Present knowledge of the nature of neutral turbulence in the winter mesosphere suggests that such turbulence cannot generate electron density fluctuations with scale-sizes as short as the 3 m needed to produce radar echoes at 52 MHz. This is particularly true as λ increases to ~100. Joint observations from ESRAD and the EISCAT 224 MHz radar suggest that PMWE is also detectable at 67 cm scale-sizes, further increasing the difficulty in explaining the echoes by neutral turbulence. Joint observations from ESRAD and lidar are also inconsistent with the expected behaviour of turbulence. Together with results concerning the thickness, echo aspect-sensitivity and echo spectral-width of the PMWE, these observation leads to the conclusion that the layers cannot be explained by turbulence alone. A role for charged aerosols in creating PMWE is proposed. The presence of aerosols is supported by the lidar observations. Upprättat; 2002; 20100922 (vicbar)